JIHÂD IN THE HADITH (STUDY OF THE INTERPRETATION OF AL-BÛTI IN THE BOOK OF AL-JIHÂD FIL ISLÂM KAIFA NAFHAMUHU WA NUMAÂRISUHU) - Fu’adi, Muhammad Farhan; Bin Madi, Faisol Nasar; Kasman, Kasman (FORUM PAEDAGOGIK, 2024)
The purpose of writing this article is to discuss the concept of jihad in al-Hadith. This research is a literature review. The researcher collected documents related to the concept of jihad in al-Hadith by analyzing the views of Muhammad Sa'id Ramadân al-Bûti through a study of the book al-Jihâd fil islâm kaifa nafhamuhu wa kaifa numârisuhu using a thematic character and descriptive-analytic approach.  The research results show that jihad has various meanings and is not focused on the meaning of war, even though in verses of the Koran there are meanings that lead to war. However, this is a form of defense, not an attack. It is recommended that future researchers be more selective in choosing the concept and type of jihad that will be studied so as not to give rise to wrong opinions, especially in maintaining the Islamic view of rahmatallilalamin.